2022
DOI: 10.18332/tid/144272
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the success of smoking cessation: A retrospective cohort study in Korea

Abstract: INTRODUCTION Every year, at least half of the smokers in South Korea attempt to quit smoking. However, the Korean smoking rate remains still high among OECD countries. This study aimed to identify the factors that influence the success of smoking cessation efforts. METHODS The study included 1395 smokers, who participated in a 12-week program comprising doctor counseling and pharmacological treatment (i.e. varenicline), conducted at smoking cessation clinics in two general hospitals from 2015 to 2019. The par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…Therefore, it appears that adding nicotine replacement therapy to varenicline treatment should be decided on Those with high nicotine addiction have difficulty quitting smoking compared to those with lower addiction levels (24). In some previous studies, it was reported that the median FTND score was higher in those who could not quit smoking, similar to our study (20,25). The main feature of nicotine addiction is the desire to feel the positive pharmacological effects of nicotine, such as psychoactive stimulation, and to avoid possible withdrawal symptoms (4).…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, it appears that adding nicotine replacement therapy to varenicline treatment should be decided on Those with high nicotine addiction have difficulty quitting smoking compared to those with lower addiction levels (24). In some previous studies, it was reported that the median FTND score was higher in those who could not quit smoking, similar to our study (20,25). The main feature of nicotine addiction is the desire to feel the positive pharmacological effects of nicotine, such as psychoactive stimulation, and to avoid possible withdrawal symptoms (4).…”
Section: Discussionsupporting
confidence: 84%
“…The reason was that older male Korean smokers have experienced more illness than younger ones, leading to a higher quit attempt rate and successful smoking cessation rate. The illnesses which had a positive effect on a successful smoking attempt included cardiovascular diseases and higher blood pressure 8 , 17 , as well as high body mass index 17 . Since expensive cigarettes reduce tobacco consumption 3 , unemployed people in our study may have had higher motivation to quit than their employed counterparts for financial reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Previous international studies show which individual-level factors influence successful smoking cessation. These factors include: taking medications and using counseling services 3 ; lifetime tobacco exposure (pack-years), education level, alcohol drinking status, and smoker’s age 7 ; severity of nicotine dependence and the presence of comorbidity (such as cardiovascular diseases and hypertension) 8 ; concerns for self-health and family’s support 9 , social pressures 9 , 10 , and encountering environments previously associated with smoking (e.g. establishments that serve alcohol) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Over recent years, successful quit smoking rates were reported as ranging from 30.2% to 45.5% [7]- [11]. A study in South Korea reported almost 40.0% of smokers accomplished smoking cessation following a 12-week quit smoking intervention [8]. In Karachi, Pakistan, a study among 330 former adult smokers, 50.3% quit successfully on their first attempt [12].…”
Section: Introductionmentioning
confidence: 99%
“…Smokers who live in urban areas have a higher chance in smoking cessation because of better access to medical facilities and more media resources for tobacco control educational campaigns, as well as higher educational attainment [20], [21]. Smokers with chronic medical illness such as hypertension, diabetes, tuberculosis, ischemic heart disease and asthma were associated with successful quit smoking and they often used more assertive choice of tobacco-cessation treatment compared to those without comorbidities [7], [8], [10], [22]- [24]. Other associated factor influencing successful quit smoking was voluntary participation in the smoking cessation service.…”
Section: Introductionmentioning
confidence: 99%